2020
DOI: 10.2147/cmar.s251297
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Hormone Therapy on the Expression of Prostate Cancer and Multi-Epigenetic Marker Genes in a Population of Iranian Patients</p>

Abstract: Background and Aim: Many recent studies have shown a direct relationship between the decrease in the expression of GSTP1 and RASSF1 with the incidence and progression of prostate cancer. Moreover, the expression level of these genes is greatly affected by epigenetic factors and their methylation pattern. Given the prevalence of prostate cancer and the importance of choosing the best method to inhibit the progression of the disease and provide specific treatment, it is important to evaluate the effect of hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…The hypomethylation of MYC's exon3 is not associated with changes in its expression; however, it was associated with a more aggressive phenotype in the examined cohort [19] . In another study and contrary to the established consensus, a group of hypermethylated genes in PCa tumors was associated with increased gene expression [20] . In an Iranian study, 35 prostate tumor samples were examined before and after hormone therapy treatment.…”
Section: Epigenetic Writerscontrasting
confidence: 60%
“…The hypomethylation of MYC's exon3 is not associated with changes in its expression; however, it was associated with a more aggressive phenotype in the examined cohort [19] . In another study and contrary to the established consensus, a group of hypermethylated genes in PCa tumors was associated with increased gene expression [20] . In an Iranian study, 35 prostate tumor samples were examined before and after hormone therapy treatment.…”
Section: Epigenetic Writerscontrasting
confidence: 60%
“…Zavridou et al (2021) revealed that the hyper-methylation of promoter and the upregulation of the expression levels of GSTP1 existed in circulating tumor cells and exosomes of mCRPC and was associated with the overall survival of PCa. Mohammadi et al (2020) indicated that GSTP1 was upregulated by hormone therapy, although we did not get a difference of GSTP1 (Figure 10C), which may be due to lack of sufficient samples. Three previous studies indicated that EFS was significantly downregulated in PCa owing to DNA methylation and was proven to be a tumor suppressor gene in PCa (Wang et al, 2020;Sertkaya et al, 2015;Vanaja et al, 2009).…”
Section: Discussionmentioning
confidence: 75%